2019
DOI: 10.46466/idj.v41i1.180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Effect of Fibers Addition on Mechanical Properties of Flexible Acrylic Resin

Abstract: Background: In chemistry the development of polymer has produced another material to poly methyl methacrylate such as epoxy resins, polyamides (nylon), acetyl resins -----etc. All these resins are suited for thermoplastic processing. Polyamide materials are more flexible than the commonly used polymethylmethacrylate. The flexibility of polyamide allows partial dentures to be pressed in one piece including clasps. Glass fibers are the most widely used reinforcing materials forming about 90 % of the reinforcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Exerted the force was gradually to ensure that the dough stage acrylic flowed evenly across the mold region. After that forces are released, then the flask is ready for curing [19].…”
Section: Flexible Acrylic Samples Preparation For Micro Vickers Hardn...mentioning
confidence: 99%
See 2 more Smart Citations
“…Exerted the force was gradually to ensure that the dough stage acrylic flowed evenly across the mold region. After that forces are released, then the flask is ready for curing [19].…”
Section: Flexible Acrylic Samples Preparation For Micro Vickers Hardn...mentioning
confidence: 99%
“…After curing, the flask permits it to cool at room temperature. When de flasking process is completed, in this time flexible resin designs are removed [19].…”
Section: Curingmentioning
confidence: 99%
See 1 more Smart Citation
“…(A Mahmoud et al, 2018) It has been shown that acrylic resin and thermoplastic denture base resins can be strengthened through the addition of a structural component of different size distributed in the acrylic matrix, thus forming a more composite structure. (Panyayong et al, 2002) (Abdul-Majeed & Hummudi, 2019 ZrO2 is a hard white amorphous powder that is obtained from zirconium which is found naturally and produced by a thermal process. ZrO2 is a material that is very resistance to crack propagation and has premium mechanical properties with high strength, fracture toughness and high thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Its worthy mention that Polymethyl methacrylate (PMMA) is the most popular denture base material due to its good esthetics, accurate fit, biocompatibility with the oral tissues, easily repaired if fractured and finally its coast is affordable. Although it has all these advantages but it has also a major drawback which is low fracture resistance that render it weak and easily fractured either when falling down or due to fatigue from long time use (5,6) Many authors suggested that strengthening of polymethyl methacrylate is possible through the addition of a structural component of different size distributed in the acrylic matrix, thus forming a strong composite structure (7,8) .…”
Section: Introductionmentioning
confidence: 99%